Gender Differences in the Routine Activities Associated With Risks for Larceny in South Korea. (August 2016) - Moon, Byongook; Morash, Merry; Jeong, SeokJin; Yoon, Hae-Sung
The present research uses data from the 2010 Korean National Criminal Victimization Survey to examine gender differences in larceny victimization and in predictors of victimization (i.e., target attractiveness, exposure to potential offenders, target hardening, guardianship, and proximity to crime and social disorder) identified by routine activity theory. The findings show no significant gender difference in general larceny victimization, suggesting that Korean females are just as likely to be victims of theft of personal belongings as males. Consistent with the theory, physical proximity to crime and social disorder are significant predictors of larceny victimization for both males and females. However, public transportation appears to have unexpected protective influences for both gender groups, showing the importance of differences in national context. Overall, the current research provides partial support for routine activity theory's applicability in explaining larceny victimization across gender groups outside of the Western context. It also raises questions about reasons for women's increasing larceny victimization rates in Korea.